Combining Ring-Opening Metathesis Polymerisation and Thiol-ene Coupling Chemistries: Facile Access to Novel Functional Linear and Non-linear Macromolecules - Lowe, Andrew; Liu, M.; van Hensbergen, J.; Burford, R. (Wiley - V C H Verlag GmbH & Co. KGaA, 2014)
The aim of this article is to highlight recent examples in which two powerful synthetic tools, namely ring-opening metathesis polymerization (ROMP) and thiol-ene (including the thiol-Michael variant) click chemistry have been combined to facilitate the preparation of novel functional materials of varying topology.